2021
DOI: 10.3390/rs13112047
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Extent of Mangrove Ecosystem Degradation by Integrating an Ecological Conceptual Model with Satellite Data

Abstract: Anthropogenic and natural disturbances can cause degradation of ecosystems, reducing their capacity to sustain biodiversity and provide ecosystem services. Understanding the extent of ecosystem degradation is critical for estimating risks to ecosystems, yet there are few existing methods to map degradation at the ecosystem scale and none using freely available satellite data for mangrove ecosystems. In this study, we developed a quantitative classification model of mangrove ecosystem degradation using freely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 64 publications
(89 reference statements)
0
28
0
Order By: Relevance
“…In September 2017, southwest Florida was hit by one such storm, classed as a Category 3 hurricane, named Hurricane Irma [20]. Studies have reported on the Hurricane Irma-induced mangrove degradation in southwest Florida [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In September 2017, southwest Florida was hit by one such storm, classed as a Category 3 hurricane, named Hurricane Irma [20]. Studies have reported on the Hurricane Irma-induced mangrove degradation in southwest Florida [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For most stakeholders (excepted one scientist), climate change was considered as a broad variable. However, it is difficult to summarize Climate change interactions with mangroves in a single variable as this corresponds to multiple factors of environmental changes (e.g., sea level rise, drought, change in salinity) that can have different-if not reverse-impacts on mangroves, depending on the context (Alongi, 2015;Lee et al, 2021). For example, in French Guiana, climate change intensifies the swell regime, which accelerates mud bank movements that should impact coastal mangroves.…”
Section: Threats On Mangroves In French Guianamentioning
confidence: 99%
“…Another useful index in characterizing mangrove intactness or degradation is the Normalized Difference Moisture Index (NDMI) (Lee et al, 2021). It is calculated as a ratio between the near-infrared (NIR) and short-wave infrared (SWIR) bands (see Table 1, Equation 4) and can be applied to determine vegetation water content (U.S. Geological Survey, 2021c).…”
Section: Vegetation and Moisture Indicesmentioning
confidence: 99%